Sarcolipin and ubiquitin carboxy-terminal hydrolase 1 mRNAs are over-expressed in skeletal muscles of α-tocopherol deficient mice - Vasu, Vihas T. (2009)
The transcriptome of ataxic muscles from α-tocopherol transfer protein deficient (ATTP-KO), 23-month old, mice was compared with that of their normal littermates. Genes encoding sarcolipin (sln) and ubiquitin carboxyl-terminal hydrolase (uchl1) were over-expressed (≥ 10-fold) in ataxic muscles. SLN is a 3.2 kDa membrane protein that binds to sarcoplasmic reticulum calcium ATPase, regulates Ca(++) transport and muscle relaxation–contraction cycles. UCHL1 is a 24.8 kDa member of proteosome proteins; it is over-expressed in myofibrillar myopathy and is associated with neurodegenerative diseases. Furthermore, six additional transcripts, three encoding thin-filament proteins and three encoding Ca(++) sensing proteins that participate in contraction-relaxation cycle, and eight transcripts that encode members of lysosomal proteins were also over-expressed in ataxic muscles. These observations suggest that chronic α-tocopherol (AT) deficiency activates critical genes of muscle contractility and protein degradation pathways, simultaneously. The magnitude of induction of sln and uchl1 was lower in asymptomatic, 8-month old, ATTP-KO mice and in 8-month old mice fed an AT-depleted diet. These studies suggest sln and uchl1 genes as novel targets of AT deficiency and may offer molecular correlates of well documented descriptions of neuromuscular dysfunctions in AT-deficient rodents. Since the neuromuscular deficits of ATTP-KO mice appear to be similar to those of patients with ATTP mutations, it is suggested that over-expression of sln and uchl1 may also contribute to AT-sensitive ataxia in humans.